“BĘDZIESZ MUSIAŁA NAUCZYĆ SIĘ GOTOWAĆ” – ROLA JEDZENIA W MODELOWANIU RELACJI MIĘDZY PACJENTEM A OPIEKUNEM W WYGRAĆ Z LOSEM W REŻYSERII JOHNA SAYLESA - Niewiadomska-Flis, Urszula (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
A transformation of hierarchical patient-caregiver relationship between May-Alice and Chantelle, complicated by racism inscribed in the relationship between a white mistress and a black helper, is negotiated through the use of food – its preparation, serving, and daily as well as festive meals. It is my intention to trace and analyze the role of food in the evolution of their relationship. I will demonstrate that food helps these women to build affectionate coexistence and meaningful communication across the color line, rather than re-inscribes racial asymmetry into their relationship through references to the served and the servant dichotomy.